JQuery design patterns : learn the best practices on writing efficient jQuery applications to maximize performance in large-scale deployments /: learn the best practices on writing efficient jQuery applications to maximize performance in large-scale deployments. ([2016]) - Greasidis, Thodoris
No abstract available